Nanoarchitectures for efficient IgE cross‐linking on effector cells to study amoxicillin allergy. Issue 10 (5th May 2021) - Tesfaye, Amene; Rodríguez‐Nogales, Alba; Benedé, Sara; Fernández, Tahía D.; Paris, Juan L.; Rodriguez, Maria J.; Jiménez‐Sánchez, Isabel M.; Bogas, Gador; Mayorga, Cristobalina; Torres, María J.; Montañez, María I.
Abstract: Background: Amoxicillin (AX) is nowadays the β‐lactam that more frequently induces immediate allergic reactions. Nevertheless, diagnosis of AX allergy is occasionally challenging due to risky in vivo tests and non‐optimal sensitivity of in vitro tests. AX requires protein haptenation to form multivalent conjugates with increased size to be immunogenic. Knowing adduct structural features for promoting effector cell activation would help to improve in vitro tests. We aimed to identify the optimal structural requirement in specific cellular degranulation to AX using well‐precised nanoarchitectures of different lengths. Method: We constructed eight Bidendron Antigens (BiAns) based on polyethylene glycol (PEG) linkers of different lengths (600–12, 000 Da), end‐coupled with polyamidoamine dendrons that were terminally multi‐functionalized with amoxicilloyl (AXO). In vitro IgE recognition was studied by competitive radioallergosorbent test (RAST) and antibody–nanoarchitecture complexes by transmission electron microscopy (TEM). Their allergenic activity was evaluated using bone marrow‐derived mast cells (MCs) passively sensitized with mouse monoclonal IgE against AX and humanized RBL‐2H3 cells sensitized with polyclonal antibodies from sera of AX‐allergic patients. Results: All BiAns were recognized by AX‐sIgE. Dose‐dependent activation responses were observed in both cellular assays, only with longer structures, containing spacers in the range of PEG 6000–12, 000 Da. Consistently, greater proportion of immunocomplexes and number of antibodies per complex for longer BiAns were visualized by TEM. Conclusions: BiAns are valuable platforms to study the mechanism of effector cell activation. These nanomolecular tools have demonstrated the importance of the adduct size to promote effector cell activation in AX allergy, which will impact for improving in vitro diagnostics. Abstract : The use of BiAns demonstrates the importance of adduct size and distance between determinants to promote effector cell activation in AX allergy. Optimal effector cell activation is showed with the biggest BiAns, which involves a greater number of immunocomplex and antibodies. BiAns are versatile nanoplatforms that can be applied to different allergies, valuable for improving in vitro allergy tests. Abbreviations: AX, amoxicillin; AXO, amoxicilloyl; BiAn, bidendron antigen; MoAb, monoclonal antibody; RBL, rat basophilic leukemia cell